Projections of disability-adjusted life years for major diseases due to a change in vegetable intake in 2017-2040 in Japan - Shiori Tanaka; Daisuke Yoneoka; Aya Ishizuka; Peter Ueda; Keiji Nakamura; Hisayuki Uneyama; Naoki Hayashi; Kenji Shibuya; Shuhei Nomura (BMC, 2021)
Abstract Background Low vegetable intake is one of the key dietary risk factors known to be associated with a range of health problems, including cardiovascular diseases (CVDs), cancer, and diabetes and kidney diseases (DKDs). Using data from Japan's National Health and Nutrition Surveys and the Global Burden of Diseases study in 2017, this study aimed to forecast the impact of change in vegetable intake on disability-adjusted life years (DALYs) between 2017 and 2040 for three diseases. Methods We generated a three-component model of cause-specific DALYs, including changes in major behavioural and metabolic risk predictors, the socio-demographic index and an autoregressive integrated moving average model to project future DALY rates for 2017-2040 using the data between 1990 and 2016. Data on Vegetable consumption and risk predictors, and DALY rate were obtained from Japan's National Health and Nutrition Surveys and the Global Burden of Diseases Study in 2017. We also modelled three scenarios of better, moderate and worse cases to evaluate the impact of change in vegetable consumption on the DALY rates for three diseases (CVDs, cancer, and DKDs). Results Projected mean vegetable intake in the total population showed a decreasing trend through 2040 to 237.7 g/day. A significant difference between the reference scenario and the better case scenario was observed with un-overlapped 95% prediction intervals of DALY rates in females aged 20-49 years (− 8.0%) for CVDs, the total population for cancer (− 5.6%), and in males (− 8.2%) and females (− 13.7%) for DKDs. Conclusions Our analysis indicates that increased vegetable consumption would have a significant reduction in the burdens of CVDs, cancer and DKDs in Japan. By estimating the disease burden attributable to low vegetable intake under different scenarios of future vegetable consumption, our study can inform the design of targeted interventions for public health challenges.